Comparative Evaluation of Onion Germplasm (Allium Cepa L.) Of Bangladesh for Physical And Antioxidant Properties (SAARC Journal of Agriculture, 2021)
Determination of antioxidant activity is one of the key elements for understanding the biological properties of a widely used spice onion (A. cepa). In contrast, physical properties help understand the textural quality of onion necessary for postharvest operations of sorting and grading in particular. Considering the physicochemical importance of onion, the present study focused on the determination of physical attributes and antioxidant content of the onion germplasm in Bangladesh using visual methods and 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, respectively. The five-onion germplasms (BARI Piaz-2, BARI Piaz-3, BARI Piaz-4, BARI Piaz-5, Faridpuri Vati) collected from selected onion growers of the Department of Agricultural Extension (DAE) of the southwestern part of Bangladesh were used as treatments for physicochemical analysis at the Horticulture laboratory of the Agrotechnology Discipline, Khulna University, Khulna, Bangladesh during the period from February to August 2019. The laboratory study was laid out in Completely Randomized Design (CRD) with three replications. Most of the physical characteristics of onion were highest in germplasm-1 than those of the other germplasm tested. The results showed that the DPPH free radicals were scavenged by all onion germplasm extracts in a concentration-dependent pattern. The highest IC50 value (238.10 ppm) was noticed in germplasm-3 and the lowest in germplasm-5 (161.29 ppm) with no statistical difference from germplasm-4 (172.41 ppm). The lower IC50 value indicating that onion germplasms-5 and -4 extracts were more potent in scavenging free radicals than the other onion germplasms. Thus, the low IC50 value facilitated the germplasm-5 and -4 to be enriched with antioxidant compounds significantly in higher amounts than the others.SAARC J. Agric., 19(1): 113-123 (2021)